Adhesive bond strength development evaluation using ABES in different lignocellulosic materials - Jorge Manuel Santos Silva Martins (2013)
This paper presents a new application of Automated Bonding Evaluation System (ABES) for studying the reactivity of adhesive-substrate combinations (adhesive-cork, impregnated paper-wood and laminate-wood); a new sample configuration and a new kinetic model are proposed. Isothermal bond strength development was plotted as a function of time for several platen temperatures and the kinetic parameters were computed from these plot families, for each type of adhesive and combinations. The methodology developed showed to have potential in quantitative screening of adhesives and operating conditions in industrial context (production of cork composites, melamine faced boards and high pressure laminates).